Micromechanical study on the origin of fiber bridging under interlaminar and intralaminar mode I failure. (15th February 2019) - Naya, F.; Pappas, G.; Botsis, J.
Abstract: Fiber reinforced polymers (FRPs) subjected to mode I fracture show important toughening due to the development of large scale bridging (LSB). Experimental studies of this phenomenon in unidirectional carbon/epoxy laminates using double cantilever beam specimens, demonstrate important differences in R-curve response for inter- and intralaminar fracture. Post fracture observation of composite's cross-section pointed out dissimilar fiber bundle size and shape, as the main origin of their differences. In the present paper, representative volume elements with the composite's constituents, based on the actual material microstructure, and homogenized 2D finite element models were developed to study the effects of microstructure on the first stage of damage leading to LSB development in carbon/epoxy composites under mode I fracture. The differences between inter- and intralaminar fracture were investigated along with the influence of fiber dispersion and the presence of interply and intraply resin-rich zones. The numerical simulations captured different microcrack morphologies for inter- and intralaminar fracture, supporting the experimental observations, while parametric studies showed the influence of the microstructure in the formation of LSB. In particular, fiber dispersion within a ply and resin rich zone between plies play significant roles in mode I fracture and can be used to control toughening mechanisms in FRPs.